Endogenous selection of comparison groups, human capital formation, and tax policy - Oded Stark; Walter Hyll; Yong Wang (University of Bonn, Center for Development Research (ZEF), 2011)
This paper considers a setting in which the acquisition of human capital entails a change of location in social space that causes individuals to revise their comparison groups. Skill levels are viewed as occupational groups, and moving up the skill ladder by acquiring additional human capital, which in itself is rewarding, leads to a shift in the individuals inclination to compare himself with a different, and on average better-paid, comparison group, which in itself is penalizing. The paper sheds new light on the dynamics of human capital formation, and suggests novel policy interventions to encourage human capital formation in the aggregate and, at the same time, reduce inter-group income inequality.
Keywords: D11; H24; H30; J24; 330; Human capital formation; Skill levels as occupational groups; Interpersonal comparisons; Relative deprivation; Tax policy; Subsidization; Humankapital; Bildungsniveau; Soziale Ungleichheit; Intelligenz; Bevölkerungsstruktur; Steuerpolitik; Steuerwirkung; Statistisches Auswahlverfahren; Theorie